LncRNA SNHG7 promotes cardiac remodeling by upregulating ROCK1 via sponging miR-34-5p - Wang, Jie (Aging (Albany NY), 2020)
Previous studies have shown that lncRNA small nuclear RNA host gene 7 (lncRNA SNHG7) played an important role in cancer progression. However, the role of lncRNA SNHG7 in cardiac fibrosis is still poorly understood. In this study, the results of quantitative real time polymerase chain reaction (qRT-PCR) analysis showed that lncRNA SNHG7 was over expressed in the infarcted and peri-infarcted area in the left ventricle after MI in mice. Western blot analysis showed that knockdown of SNHG7 decreased the expression of collagen type 1 (Col1)and α-smooth muscle actin (α-SMA). Echocardiographic study suggested that inhibition of SNHG7 improved cardiac function after MI in mice. Luciferase assay indicated SNHG7 could act as a competing endogenous RNA (ceRNA) by sponging miR-34-5p. The MTT cell proliferation assay and 5-ethynyl-2’-deoxyuridine (EdU) labelling assay revealed that co-transfection of SNHG7 and miR-34-5p inhibited cell viability and proliferation of cardiac fibroblasts (CF). All the results indicated that lncRNA SNHG7 could promote cardiac fibrosis via targeting miR-34-5p through acting as a ceRNA in mice after MI. Silencing of SNHG7 could attenuate deposition of collagens and improve cardiac function. miR-34-5p could suppress the fibrogenesis of CF by targeting ROCK1 and abolish SNHG7-induced CF proliferation and fibroblast-to-myofibroblast transition.